1994
DOI: 10.1007/bf01258466
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent effects of E-4031, almokalant, dofetilide and tedisamil on action potential duration: no evidence for “reverse use dependent” block

Abstract: Antiarrhythmic drugs with class III action are incriminated by "reverse use dependency" which implies preferential block of resting channels (Hondeghem and Snyders 1990). The purpose of the present study was to investigate the frequency dependence of the effects of four new antiarrhythmic compounds on action potential duration (APD) in guinea-pig papillary muscle and on delayed rectifier in guinea-pig ventricular myocytes in order to scrutinize the concept of reverse use dependency and to obtain evidence for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…1,3,4 It does not occur in resting muscle but rather develops on depolarization. 1,5 Recovery from block is also potential dependent and is very slow at hyperpolarized potentials close to the resting potential. 1 Steady-state block at any dose is constant and does not change with increasing heart rate 1,3 because the recovery time is much greater than the diastolic interval.…”
Section: Effects Of Dofetilide On I Krmentioning
confidence: 99%
“…1,3,4 It does not occur in resting muscle but rather develops on depolarization. 1,5 Recovery from block is also potential dependent and is very slow at hyperpolarized potentials close to the resting potential. 1 Steady-state block at any dose is constant and does not change with increasing heart rate 1,3 because the recovery time is much greater than the diastolic interval.…”
Section: Effects Of Dofetilide On I Krmentioning
confidence: 99%
“…It has been recently suggested that dofetilide interacts with the channels in both the open and the inactivated states [17]. The interaction between dofetilide and receptor presents a very slow kinetics [11,13] and exhibits reverse use-dependence [2,16]. The increment in the dofetilide dose enhances the reverse-use dependence [2].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidences suggest that the interaction between the drug and the receptor in the channel is produced in the open state (open channel block) rather than in the closed state [3,13,16]. Once the block has been produced, the effect persists during a long period at rest, suggesting that the drug does not dissociate when the channel is closed; the drug seems to be trapped within the channel [3,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations